An Analysis of the Development of EFL Students’ Communicative Competence Based on Technological Knowledge in Higher Education - Rinantanti, Yulini; Ibrahim, Muliaty; Sujarwo, Sujarwo; Nemo, Maximus L; Wally, Andri R (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
Pedagogical competency is essential in influencing the growth of EFL students within the educational context. This research aims to analyze the development of EFL students' communicative competence based on technological knowledge in higher education. This research used a descriptive qualitative research method. The numbers of respondents of this study were twenty EFL students by using stratified sample technique from ninety EFL students. The results of the study show what contexts students use to voice their opinions, ranging from talks about general topics (education policy, movies, everyday events) to talks about organizations, lecturing, in-class presentations, public presentations, and the final category, using media technologies (chats, recordings, and video recordings). The students reported feeling comfortable and motivated to engage with media technology. Pedagogical technologies might support EFL students in enhancing their communicative competence. Pedagogical technologies have the potential to motivate students to adopt a self-directed learning style and collaborate to enhance their communicative competence by providing them with access to a learning environment outside of the traditional classroom.